دراسة تفاعلية تداولية في الخطاب الاجتماعي في وسائل التواصل: الفيسبوك نموذجاً /Interactive and Pragmatic Study of Social Discourse in Social Media: Facebook as Case Study of - Elsiddig Adam Barakat, (مجلة الدراسات اللغوية والأدبية (Journal of Linguistic and Literary Studies), 2023)
ملخص البحث: موضوع هذا البحث تحليل الخطاب الاجتماعي لدى الشباب السوداني الناشط في وسائل التواصل الاجتماعي وخاصة (الفيسبوك)، وتم تحليلها تداولياً وتفاعلياً، وقد اخترنا عينة البحث من كتابات الشباب عن الفيضانات التي اجتاحت السودان في خريف عام 2020م، والتي أحدثت خسائر كبيرة، وشكلت اهتماماً كبيراً للرأي العام والإعلام. وخلص هذا البحث إلى نتائج عديدة من أهمها: بنى الخطاب عينة البحث من تآلف مفردات من اللغة العربية في مستواها الفصيح ممزوجة بمفردات من اللهجة العامية السودانية؛ لأن الأخيرة في بعض الأحيان تستعمل لتوصيل معانٍ مقصودة، وإحداث تفاعل مرجو، وتداول يقصده مدون الخطاب، كما أن طبيعة الخطاب الاجتماعي للشباب السوداني في الفيسبوك الذي دوِّن في محنة السيول والفيضانات في أغلبه تفاعلي، ولا يهتم بحفظ المقامات ولا يراعيها، فمدون الخطاب من عامة الناس، ويستهدف به العامة، ومن هم أرفع منه وأدنى منه على حدٍ سواء، وأكدت الدراسة على تبني الأجندة الحرة في تدوينات الشباب السوداني في الفيسبوك في الفيضانات والسيول، وانصب العرض والنقاش في الخطاب الذي تم دراسته في هذا البحث على الموضوع؛ أي المعنى لا الشكل. الكلمات المفتاحية: تحليل الخطاب، البعد الاجتماعي، وسائل التواصل، التفاعل، التداولية. Abstract: This research is an analysis of the social discourse of Active Sudanese youth in social media, especially (Facebook). Using pragmatic and interactive method, research sample was selected from youth writings on the floods that swept Sudan in the rainfall of 2020 AD, which caused great losses and constituted great attention to public opinion and the media. This research concluded with many results, the most important of which are: The discourse of the research sample was built from a combination of vocabulary from the Arabic language at its standard level mixed with vocabulary from the Sudanese colloquial dialect; because the latter is sometimes used to convey intended meanings, to create a desired interaction, and deliberation intended by the letter's writer. Likewise, the nature of the social discourse of Sudanese youth on Facebook, who wrote about the ordeal of torrents and floods, is mostly interactive and does not care about preserving sacred level and does not take them into account. The writer of the speech is from the public, and he targets the public and those who are both higher and lower than him. The study confirmed the adoption of a free agenda in the posts of Sudanese youth on Facebook regarding floods and torrents, and the presentation and discussion of the discourse that was studied in this paper focused on the topic (i.e. the meaning), not the form. Keywords : Discourse Analysis , Social dimension, Social media, Interaction, Pragmatics Abstrak Kajian ini menganalisa wacana sosial remaja Sudan yang aktif dalam media sosial khususnya Facebook. Menggunakan pendekatan pragmatik dan interaktif, kajian ini memilih sampel kajian dari penulisan belia berkenaan bencana banjir yang melanda Sudan ketika hujan lebat yang berlaku pada tahun 2020 dan menyebabkan kerugian besar dan mendapat perhatian meluas dari orang awam dan media. Kajian ini menyimpulkan beberapa dapatan, antaranya ialah: Sampel kajian terbentuk daripada gabungan kosa kata daripada bahasa Arab standard dan kosa kata daripada dialek bahasa Arab Sudan. Penggunaan dialek tempatan kadangkala digunakan untuk menyampaikan makna tertentu, dan dilihat mampu menghasilkan interaksi dan makna tertentu yang terhasil mengikut konteks (pragmatik) seperti yang dimaksudkan oleh penulis ucapan. Selain itu, sifat wacana sosial belia Sudan di Facebook kebanyakannya bersifat interaktif. Ini kerana ia ditulis dalam konteks bencana banjir. Wacana sosial Sudan juga tidak mementingkan aspek estetika luaran, kerana pengkaryanya adalah terdiri dari rakyat kebanyakan. Wacana seperti ini turut digunakan oleh golongan yang elit mahupun yang rendah. Kajian ini mengikuti aspirasi anak muda Sudan melalui Facebook dalam mendepani bencana banjir. Fokus penyampaian dan perbincangan dalam wacana yang dikaji dalam penyelidikan ini adalah kepada topik atau makna dan bukan pada format wacana tersebut. Kata kunci: analisis wacana, dimensi sosial, media sosial, interaksi, pragmatik